Weather Shock, Agricultural Productivity and Infant Health: A Tale of Environmental Injustice - Soumya Pal (Global Labor Organization (GLO), 2021)
We study how income shock affect due to weather shock causally impacts the birth outcomes. We selected households depended directly on agriculture due to their extreme vulnerability to temperature and rainfall shocks. We find large efficiency loss attributed to weather shock for major food crops to the extent of 20%. However, we find that access to technology provides resilience against weather shock, therefore, causing the heterogeneity in vulnerability across farming households. Based on it, we designed the agriculture-household model, which predicts that health outcomes of child is dependent on income shock due to change in weather conditions. We tested the hypothesis by introducing weather shock in the cropping season before the conception of child to elim- inate the confounding effect of direct impact due to extreme weather conditions. We find that weather shocks in cropping season, increases the likelihood of child mortality, low birth weight, and birth size. We further find that access to technology, financial tools, and economic security net reduces the impact of income loss due to weather shock. Our results suggests that access to resilient capabilities leads to heterogeneous impact across farmer households causing environmental injustice. Further, our findings provide insights into the policy design for long term shift in weather patterns due to climate change and stresses on the inequality in resilience against extreme weather events.
Keywords: Q1; Q5; I1; I3; D1; 330; Environmental Justice; Weather Shock; Farm Income; Child Mortality